H-N2N : uma arquitetura hierárquica escalável para ambientes de realidade mista de grande porte - Burlamaqui, Aquiles Medeiros Filgueira (2008)
In this work, we propose a solution to solve the scalability problem found in collaborative, virtual and mixed reality environments of large scale, that use the hierarchical client-server model. Basically, we use a hierarchy of servers. When the capacity of a server is reached, a new server is created as a sun of the first one, and the system load is distributed between them (father and sun). We propose efficient tools and techniques for solving problems inherent to client-server model, as the definition of clusters of users, distribution and redistribution of users through the servers, and some mixing and filtering operations, that are necessary to reduce flow between servers. The new model was tested, in simulation, emulation and in interactive applications that were implemented. The results of these experimentations show enhancements in the traditional, previous models indicating the usability of the proposed in problems of all-to-all communications. This is the case of interactive games and other applications devoted to Internet (including multi-user environments) and interactive applications of the Brazilian Digital Television System, to be developed by the research group. Keywords: large scale virtual environments, interactive digital tv, distributed